WOMEN POWER TO END THE OPPRESSIONS OF PATRIARCHY IN SUSAN GLASPELLÃ¢â¬â¢S PLAY Ã¢â¬ËTRIFLESÃ¢â¬â¢ - Asianti, Dwi Anggara (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2012)
In patriarchy society, women do not have other choice but obey all rules set by men. As a result, womenÃ¢â¬â¢s life marginalized and gap between womenÃ¢â¬â¢s role and menÃ¢â¬â¢s occurred.The same condition and situation faced by a woman, as the main character, in Susan GlaspellÃ¢â¬â¢sÃÂ entitled Ã¢â¬ËTriflesÃ¢â¬â¢. This paper would like to identify the patriarchy oppressions and analyze action as the reflection ofÃÂ womenÃ¢â¬â¢s power to end the oppressions of patriarchy. The women power, subtle and indirect, that may the women themselves never realize they have it